2019
DOI: 10.1002/jbm.a.36792
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammation effects of injectable platelet‐rich fibrin via macrophages and dendritic cells

Abstract: Immune response to implantation materials plays a critical role during early local inflammation and biomaterial-induced regeneration or restoration. A novel platelet concentrate termed i-PRF (injectable platelet-rich fibrin) has recently been developed without any additives by low centrifugation speeds. To date, scientists have investigated the capability of releasing growth factors to improve regeneration but have ignored whether i-PRF can inhibit the inflammatory effect around the wound. The present study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 34 publications
2
63
0
2
Order By: Relevance
“…In contrast, early osteogenesis began to occur under the SM in group A-PRF ( Figures 5A,B). As previously noted, bioactive factors in A-PRF suppress inflammation, and the low-inflammatory microenvironment favored continuous selfrenewal of the sinus cavity in group A-PRF (Nasirzade et al, 2020;Zhang et al, 2020) and reached a dynamic balance between bone formation and resorption. In addition, the significant amount of growth factors and cytokines within A-PRF also played an essential role in regulating the bone remodeling process (Marx, 2004;Aminabadi, 2008;Peerbooms et al, 2010;Soloviev et al, 2014;Herath et al, 2018).…”
Section: Discussionsupporting
confidence: 58%
“…In contrast, early osteogenesis began to occur under the SM in group A-PRF ( Figures 5A,B). As previously noted, bioactive factors in A-PRF suppress inflammation, and the low-inflammatory microenvironment favored continuous selfrenewal of the sinus cavity in group A-PRF (Nasirzade et al, 2020;Zhang et al, 2020) and reached a dynamic balance between bone formation and resorption. In addition, the significant amount of growth factors and cytokines within A-PRF also played an essential role in regulating the bone remodeling process (Marx, 2004;Aminabadi, 2008;Peerbooms et al, 2010;Soloviev et al, 2014;Herath et al, 2018).…”
Section: Discussionsupporting
confidence: 58%
“…In addition, the effects of GNPs‐iPRF on cellular immunity, migration, and the mechanical strength of materials on cell differentiation have not been explored in this study. Among previous studies, it was shown that in addition to promoting angiogenesis, various growth factors within iPRF could also promote cell proliferation, cell migration, and regulate the macrophages to transform to the anti‐inflammation state . It was also proven that mechanical features such as stiffness, stress relaxation, and creep can significantly steer stem cell fate .…”
Section: Resultsmentioning
confidence: 99%
“…Along with the platelet growth factors, like that of PRP, 4 this product also documents to contain lymphocytic growth factors and collagen type1. 5 It also produces fibrin network like PRF membrane. 6 Its unique property is that it stays as a liquid for a period of approximately 20 minutes after which the fibrin polymerization takes place and a solid membrane is formed.…”
Section: Discussionmentioning
confidence: 99%